2017
DOI: 10.1159/000481147
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Renal Function on Treatment Results after Stroke Thrombectomy

Abstract: Background: Renal dysfunction (RD) may be associated with poor outcome in ischemic stroke patients treated with mechanical thrombectomy (MT), but data concerning this important and emerging comorbidity do not exist so far. Here, we investigated the influence of RD on postprocedural intracerebral hemorrhage (ICH), clinical outcome, and mortality in a large prospectively collected cohort of acute ischemic stroke patients treated with MT. Methods: Consecutive patients with anterior-circulation stroke treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(71 citation statements)
references
References 32 publications
(67 reference statements)
8
54
0
Order By: Relevance
“…Due to the lack of imaging data, we can only speculate that a higher rate of infratentorial cerebral microbleeds may be the cause of the observed association of RD with ICH in our cohort. While no association between RD and postprocedural ICH was observed in a former study of patients with anterior circulation stroke [5], further studies, evaluating a possible influence of cerebral microbleeds in these patients, would be desirable. Interestingly, we observed a strong trend toward an association between delayed groin puncture and ICH, which is in accordance to a previous study, reporting an association between symptomatic ICH and symptom-to-groin times that exceeded 270 min [21].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Due to the lack of imaging data, we can only speculate that a higher rate of infratentorial cerebral microbleeds may be the cause of the observed association of RD with ICH in our cohort. While no association between RD and postprocedural ICH was observed in a former study of patients with anterior circulation stroke [5], further studies, evaluating a possible influence of cerebral microbleeds in these patients, would be desirable. Interestingly, we observed a strong trend toward an association between delayed groin puncture and ICH, which is in accordance to a previous study, reporting an association between symptomatic ICH and symptom-to-groin times that exceeded 270 min [21].…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, due to limited numbers, a detailed statistical analysis on symptomatic and fatal ICHs was not reasonable, and our results remain descriptive. We cannot exclude that a selection bias may have contributed to differing results between anterior [5] and posterior circulation stroke patients and because of the observational character of our analysis, we did also not perform a prespecified power analysis. We can also not exclude that the overall restricted number of cases may have contributed to our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous observational studies investigated the relationship between renal function and stroke outcomes. However, only one study included MT patients and their results were conflicting [4][5][6][7][8][17][18][19][20][21]. Some studies found that reduced eGFR significantly increased the risk of stroke mortality [4,5] and it was associated with poor outcome and sICH after intravenous thrombolysis [6].…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies may be explained by the following reasons. First, the stroke type, some studies included both ischemic and hemorrhagic stroke [5,7,18,19], while others were one type only [4,6,8,17,20,21]. Second, different onset time.…”
Section: Discussionmentioning
confidence: 99%